ANALISIS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DI SEKTOR PELAYANAN KESEHATAN DALAM PERSPEKTIF HUKUM PIDANA DAN HUKUM ADMINISTRASI NEGARA - Mhd. Ihwanuddin Hasibuan; Ardina Fariani Lubis (Berajah Journal, 2026)
Corruption in the healthcare sector is a serious problem that threatens the fundamental right of citizens to quality healthcare services. This study aims to analyze law enforcement against corruption in the healthcare sector from the perspectives of criminal law and state administrative law in Indonesia. A normative legal research method is employed using a statutory and conceptual approach. The findings reveal that law enforcement still faces significant challenges, including overlapping authority among the KPK, Attorney General's Office, and Police; weak internal oversight mechanisms; and a lack of transparency in healthcare procurement. From a criminal law perspective, Law No. 31/1999 as amended by Law No. 20/2001 needs to be synergized with administrative sanction mechanisms to create comprehensive deterrence. The study concludes that institutional reform, strengthened law enforcement capacity, and regulatory harmonization between criminal and administrative law are urgently needed.